2013
DOI: 10.6026/97320630009464
|View full text |Cite
|
Sign up to set email alerts
|

An-Overview on invertase in sugarcane

Abstract: Saccharum officinarum is one of the most cultivated hybrid varieties among the sugarcane varieties. In sugarcane plant sucrose is the major carbohydrate which can be stored and transported. Different physiological and biochemical studies on this crop report that invertase activity and sucrose concentration some how are key limiting step in the process of sucrose accumulation. Significant efforts have been made in relation to the sucrose cycle by altering the sucrose phosphate synthetase, sucrose synthetase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…The invert syrup is used in food and beverage industries as a humectant in the preparation of candies, noncrystallizing creams, jams and artificial honey. 5 , 6 It is reported in the present study A. niger simultaneously produces intra-extracellular inulinase and invertase, which offers a great advantage to industry, particularly the food industry, for production of ultra-high fructose syrup, bio-ethanol, inulo-oligosaccharide, single-cell oil, single-cell protein, citric acid, butanediol, alcohols and lactic acid from inulin and sucrose by a single-step process. 7 , 8 , 9 , 10 Since many enzymes of industrial significance are regulated by the medium composition and fermentation conditions, a study of such regulation is of prime importance for the commercial production of such enzymes.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…The invert syrup is used in food and beverage industries as a humectant in the preparation of candies, noncrystallizing creams, jams and artificial honey. 5 , 6 It is reported in the present study A. niger simultaneously produces intra-extracellular inulinase and invertase, which offers a great advantage to industry, particularly the food industry, for production of ultra-high fructose syrup, bio-ethanol, inulo-oligosaccharide, single-cell oil, single-cell protein, citric acid, butanediol, alcohols and lactic acid from inulin and sucrose by a single-step process. 7 , 8 , 9 , 10 Since many enzymes of industrial significance are regulated by the medium composition and fermentation conditions, a study of such regulation is of prime importance for the commercial production of such enzymes.…”
Section: Introductionmentioning
confidence: 67%
“…Invertase has a role in the metabolism, sucrose storage, as catalytic in the conversion of sucrose into glucose and fructose, produces invert syrup, which contains glucose and fructose at equimolar concentrations. The invert syrup is used in food and beverage industries as a humectant in the preparation of candies, noncrystallizing creams, jams and artificial honey 5, 6. It is reported in the present study A. niger simultaneously produces intra-extracellular inulinase and invertase, which offers a great advantage to industry, particularly the food industry, for production of ultra-high fructose syrup, bio-ethanol, inulo-oligosaccharide, single-cell oil, single-cell protein, citric acid, butanediol, alcohols and lactic acid from inulin and sucrose by a single-step process 7, 8, 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…These sucrose metabolizing enzymes in sugarcane genotypes are diversely affected during different growth stages (Tana et al 2014). It has been investigated that accumulation of sucrose in sugarcane tissue is mainly dependent on invertase and SPS activities which are adversely affected by climatic alterations (Ansari et al 2013). However, these climate changes are reported to have a substantial impact on crop production ultimately leading to yield losses with great risk for future global food security (Christensen & Christensen 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that as soon as sugarcane is harvested, bacteria cause acidification of the product by transforming sugars and storage substances (starch, cellulose) [4]. This acidification favors a biological and chemical phenomenon in the presence of invertases widely distributed in the biosphere and mainly isolated from sugarcane (S. officinarum) and micro-organisms such as Saccharomyces cerevisiae [5,6]. It is therefore imperative to determine if the loss of sucrose is due to the invertase activity of the yeast S. cerevisiae present in the juices and also to determine the characteristics of the juices of different varieties of sugarcane used.…”
Section: Introductionmentioning
confidence: 99%